1993
DOI: 10.1159/000154677
|View full text |Cite
|
Sign up to set email alerts
|

Two Rat Middle-Piece Coating Antigens Are Lost upon in vitro Capacitation

Abstract: The rat sperm-binding antigen, CFS, contains two subunits, RSV IV and RSV V. Sperm-bound RSV IV was previously detected using anti-RSV IV antibodies, while the presence of RSV V on the cell surface was doubtful. The RSV V subunit was purified from rat seminal vesicle secretion by gel filtration and ionic exchange chromatography. Rabbit polyclonal mono-specific antibodies against either RSV IV or RSV V were used to monitor the binding of the CFS complex onto the rat spermatozoa in indirect immunofluorescence ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Binding of the rat CFS antigen to the tail region of buffalo epididymal spermatozoa and the identification of buffalo CFS-like antigens on the same region of ejaculated spermatozoa suggest that the sperm-protein interaction has been mantained, during evolution, in the two species. As already mentioned, the CFS antigen was suggested to inhibit motility of rat sperm (Bergamo et al, 1993). In fact, addition of a protein fraction containing the CFS subunits decreased the motility of rat epididymal spermatozoa (Pietz & Mabee, 1990).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Binding of the rat CFS antigen to the tail region of buffalo epididymal spermatozoa and the identification of buffalo CFS-like antigens on the same region of ejaculated spermatozoa suggest that the sperm-protein interaction has been mantained, during evolution, in the two species. As already mentioned, the CFS antigen was suggested to inhibit motility of rat sperm (Bergamo et al, 1993). In fact, addition of a protein fraction containing the CFS subunits decreased the motility of rat epididymal spermatozoa (Pietz & Mabee, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…The rat seminal vesicle secretory protein CFS, so called because it is a Complex constituted by the subunits RSV IV and RSV V (also known as proteins F and S, respectively) (Manco et al, 1989), was found capable of binding in vitro to epididymal spermatozoa and was extracted from ejaculated spermatozoa . This sperm-coating antigen was localised on the tail of decapacitated cells and was lost upon capacitation (Bergamo et al, 1993). In rat, previous data on sperm motility inhibition by a CFS-containing protein fraction from seminal vesicle fluid (Peitz & Mabee, 1990) suggest that CFS might play a role in regulating flagellar movement.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation